Christopher I. Becwith, The Tibetan Empire in Central Asia: A History of the Struggle for Great Power among Tibetans, Turks, Arabs and Chinese during the Early Middle Ages. Princeton, Princeton University Press, 1987, xviii + 269 pp. - Hernán Taboada (El Colegio de México, A.C., 1990)
-